Integrating environmental costs when calculating the energy efficiency potential - Sonja Arnold-Keifer; Jasper Müller; Tim Mandel (Cleaner Environmental Systems)
Environmental pollution results in high costs for society in terms of transformation measures and adaptation to climate change. One way to directly measure and evaluate the impact of products, technologies and services on the environment is to introduce environmental costs. These costs can also be considered as avoided costs when it comes to savings opportunities. Integrating environmental costs in energy efficiency potential calculations allows stakeholders and decision-makers to compare the outcomes of different opportunities and can help to allocate the occurring damage directly to the consumer in order to create incentives. This paper incorporates environmental costs for greenhouse gas and air pollution emissions into the energy cost curve (CSC) by adding environmental damage costs of electricity generation to the energy price. Specifically, an environmental damage cost of electricity generation of 2.67 EUR-ct2022/kWh, with variations explored in a sensitivity analysis. Accounting for these environmental costs reduces the specific costs of conserved energy (SCCE), demonstrating a positive effect on the economic viability and cost-effectiveness of energy efficiency measures, and providing a more accurate assessment of the true impact of environmental pollution.